Exploring reproduction (or is it procreation?) over language boundaries: the challenges and hidden opportunities of translation. (November 2020) - Bateman, Simone
Abstract: This article addresses the challenges and benefits derived from having to present social science research in another language than one's usual working language. As objects of study are, in part, moulded by language, translation becomes an invaluable opportunity for critical reflection on our epistemic choices. The article thus proposes a brief inquiry into the words we use, in French and in English, to describe and discuss issues in assisted reproductive technology, or medically assisted procreation as one would say in French. The article first explores similarities and differences in the generic terms used in each language to refer to this area, and discusses the verbs used to describe different facets of the reproductive process. It then proposes a short discussion of two terms often used interchangeably in both languages, 'reproduction' and 'procreation', and introduces a third term, engendrement ('engendering') that has recently emerged in France as an alternative concept. The conclusion points to the impact that technology may have on the issues considered worthy of attention, and on the meaning of certain words, as reproductive acts are displaced from the body to the laboratory. It also urges greater attention to how language affects the way we conceptualize reproductive practices and issues, and to how we deal with these differences in international encounters.